Epidural adipose tissue-derived mesenchymal stem cell activation induced by lung cancer cells promotes malignancy and EMT of lung cancer - Yan Wang (Stem Cell Research & Therapy, 2019)
Abstract Background Spinal metastasis is a major challenge in patients with advanced lung cancer, but the mechanisms in the organotropism of metastasis are still unclear. Adipose-derived mesenchymal stem cells (ADSCs) exhibit cancer-promoting properties that influence the tumour microenvironment; however, there is no research on ADSCs from epidural fat thus far. Methods In this study, we isolated and identified ADSCs from epidural adipose tissue for the first time. We examined the activation of epidural ADSCs treated with lung cancer cell-conditioned medium by immunohistochemistry, western blot and qRT-PCR assays. The expression of interleukin (IL)-6 family cytokines in the supernatants of ADSCs were evaluated by enzyme-linked immunosorbent assay. The effects of epidural ADSCs on the growth and invasion of lung cancer cells were evaluated with the CCK-8 and Transwell assays. The expression of signal transducer and activator of transcription 3 (STAT3), matrix metalloprotease and epithelial-mesenchymal transition markers were measured by western blot assays. Results Our results showed that ADSCs treated with lung cancer cell-conditioned medium expressed higher levels of the myofibroblast marker α-smooth muscle actin and fibroblast activation protein than ADSCs cultured alone. Then, we found that lung cancer cells induced ADSCs to secrete high levels of IL-6 family cytokines and activate the STAT3 signalling pathway. Moreover, activated epidural ADSCs exhibited the ability to promote lung cancer cell proliferation and invasion by elevating matrix metalloprotease expression and epithelial-mesenchymal transition in cancer cells. Furthermore, blocking IL-6 can counteract the differentiation and tumour-promoting effects of ADSCs. Conclusion Our results suggest that ADSCs respond to lung cancer cells and are involved in the crosstalk between primary tumours and pre-metastatic niches in epidural fat.